Systematic Literature Review Based on Big Data: Mindful Parenting of Working Mothers in the Context of Early Childhood Parenting: Mindful Parenting of Working Mothers in the Context of Early Childhood Parenting - Badi'atul Husna; Ika Andrini Farida (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
This study examines the influence of mindful parenting on emotional regulation in early childhood through a systematic literature review of research articles published between 2020 and 2024. The research method employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach for article selection and screening in Scopus and Google Scholar databases. From an initial 759 articles, 10 met the inclusion criteria and were thematically analyzed. Findings indicate that mindful parenting plays a significant protective role in enhancing children's emotional regulation, reducing parental stress, and improving parent-child interaction quality. Mindful parenting-based interventions and psychometric instruments were also found valid and effective across cultural contexts. This study provides theoretical and practical contributions by strengthening the conceptual framework of mindful parenting and offering culturally relevant directions for intervention development. Its practical implication is the development of mindful parenting-based intervention programs to support family well-being and optimal emotional development in children